Dependent or Independent? A Deep Dive into Students' Clause Identification - Magvirah Octasary; Novita Pratiwi; Sri Ayu Budi Lestari (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The purpose of this study was to assess the capacity of Khairun University English Language Education students in their fifth semester to use independent and dependent clauses in complicated sentences. The emphasis was on distinguishing between intransitive and transitive independent sentences, as well as adverbial, adjectival, and nominal dependent clauses. A descriptive qualitative research approach was used with 33 fifth-semester students. A written test was used to collect data, with an interview serving as additional assistance. The average score for student' ability to use independent clauses was 59.64, which was classified as fair. In comparison, the average score for dependent clause usage was 60.27, which was classified as good. Overall, the students' average score for employing independent and dependent clauses was 62.12, indicating strong overall aptitude. Based on these data, Students demonstrated a stronger ability in identifying dependent clauses compared to independent clauses. Therefore, further research is needed to explore effective techniques, methods, or learning media that can enhance students' ability to identify clauses, particularly independent clauses